Optimizing Customer Engagement: The Impact of Gamification Elements on Customer Stickiness in Shopee Games - Ningtyas, Lista Ayu; Atmaja, Ferry Tema (Universitas Negeri Semarang, 2024)
This research is aimed for analyzing the influence of reward element, challenge element, and customer engagement toward customer stickiness. However, gamification in marketing is becoming increasingly popular and has successfully captured customer interest on e-commerce platforms. Shopee, for example, has introduced gamification features through Shopee Games. On top of that, research on the impact of gamification elements in Shopee Games on customer engagement and stickiness is still limited. This quantitative study utilizes primary data from 130 active Shopee users and Shopee Games players through an online questionnaire. Data analysis using SmartPLS4 indicates that rewards and challenges in Shopee Games positively contribute to user engagement. However, only challenges influence long-term engagement and user stickiness. Satisfying gaming experiences and intriguing challenges form a strong emotional bond with Shopee Games, encouraging prolonged participation. These findings not only provide insights into the relationship between gamification, engagement, and customer stickiness in Shopee Games but also open opportunities to strategically implement gamification to effectively enhance long-term customer engagement and stickiness.